Dampak Kebijakan Work From Home Terhadap Prestasi Kerja Pegawai Pemerintah Non Pegawai Negeri Satuan Kerja Pelaksanaan Jalan Nasional Wilayah I Provinsi Jawa Tengah Tahun 2020 - Thyo Endratmoko; Sri Rahayu (BISECER (Business Economic Entrepreneurship), 2022)
Work Perfomance at WFH policy of PPNPN Satker Pelaksanaan Jalan Nasional Wilayah I Provinsi Jateng is greatly influenced by discipline, creativity and responsibility. The problems in thisÂ  research is to knowing the effect of discipline, creativity and responsibility at WFH Policy on Work Perfomance of PPNPN Satker Pelaksanaan Jalan Nasional Wilayah I Provinsi Jateng. In this study the type of research used is explanatory research. The population referred to in this study are 134 employees. The results of a simple correlation analysis for disciplne variables on work perfomance obtained tcount 2.668, creativity on work perfomance obtained tcount 4.943 and responsibility on work perfomance obtained tcount 3.753. Based on the calculated F test obtained Fvalue 443,10. The conclusion from this research is Discipline, Creativity and Responsibility at WFH Policy have an significant effect on Work Perfomance of PPNPN Satker Pelaksanaan Jalan Nasional Wilayah I Provinsi Jateng, both of partially and simultaneously.